THE IMPORTANCE OF THE “MYPROLAB.UZ” PROFESSIONAL DIAGNOSTICS PLATFORM IN THE PROFESSIONAL CHOICE OF SCHOOL STUDENTS AND ITS ORGANIZATION (Universal International Scientific Journal, 2026)
This thesis provides a comprehensive analysis of the socio-psychological foundations of the formation of a conscious and correct professional choice of schoolchildren. It also substantiates the need to use modern digital technologies in the process of students' professional self-awareness. In particular, the role of the "MyProLab.uz" professional diagnostic platform in identifying the individual characteristics of students, adapting them to professions, and forming professional motivation is scientifically and practically highlighted. The possibilities of increasing the effectiveness of professional guidance as a result of the platform's integration into the education system are shown.
Keywords: professional choice, career guidance, psychological diagnostics, students, motivation, abilities, digital technologies, MyProLab, individual approach